PrP-dependent association of prions with splenic but not circulating lymphocytes of scrapie-infected mice. - Raeber, A J (1999)
An intact immune system, and particularly the presence of mature B lymphocytes, is crucial for mouse scrapie pathogenesis in the brain after peripheral exposure. Prions are accumulated in the lymphoreticular system (LRS), but the identity of the cells containing infectivity and their role in neuroinvasion have not been determined. We show here that although prion infectivity in the spleen is associated with B and T lymphocytes and to a lesser degree with the stroma, no infectivity could be detected in lymphocytes from blood. In wild-type mice, which had been irradiated and reconstituted with PrP-deficient lymphohaematopoietic stem cells and inoculated with scrapie prions, infectivity in the spleen was present in the stroma but not in lymphocytes. Therefore, splenic B and T lymphocytes can either synthesize prions or acquire them from another source, but only when they express PrP.